Minat Masyarakat dalam Bidang Pertanian â€œKasus Masyarakat Kampung Udapi Hilir Kabupaten Manokwari, Papuaâ€ - Yolanda Holle (Jurnal Penyuluhan, 2023)
The absorption of employment in agriculture is the focal point of the problem, where the interest in working is important. This research examines people's interest in agriculture; analyze attitudes, subjective norms, and social control in agriculture; analyze the relationship of attitudes, social norms, social control, and characteristics of respondents to community interest. The research was conducted in Udapi Hilir Village, Manokwari Regency using a survey method to 94 respondents. Data analysis using simple tabulation and partial least square test. The results of the study conclude that the community is not interested in being a provider of production facilities and administrators of farmer groups but is interested in becoming farmers and farm laborers. The attitude agrees that agriculture requires high labor, high production costs, risk of failure, and requires storage space. People's subjective norms that agriculture is the main source of livelihood, food source, and requires a large areal of land. Social control in the form of production inputs and subsidies for production costs from the government. Farming experience, productive age, production facilities assistance, production facilities cost subsidies, and production marketing assistance affect interest in farming.